معايير النصية في النصوص المترجمة : دراسة نصية تقابلية لنصوص سياسية مختارة (مترجمة من الإنجليزية لإلى العربية( في قضايا الشرق الأوسط - لوال نوح او. جينادو (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2008)
Translation Studies is replete with different kinds of theories and methods which are proposed to assist in the practice of Translation, in spite of the practical value of these theories, there exist some translational problems resulting from textual decoding and analysis, transfer of textual meaning, evaluation of translated texts and assessment of translational equivalence. A Textlinguistic approach has been considered a pragmatic touchstone for translation studies and translation criticism owing to its multidisciplinary nature and its focus on empirical text-based analysis. The instrumentality of its standards to the effective analysis of natural texts cannot therefore be overemphasized. This research work however contributes to the subject by discussing the text-linguistic constitutive and regulative standards and highlighting their practical significance to the analysis of real texts. It also surveys concepts and standards of textuality in Arabic linguistic and literary traditions. The work relates the principles and its usefulness to the process(es) of translation. It essays transforming the standards into a cognitive frame of reference for the analysis and evaluation of real Translation. The research practically and specifically applies the standards on some selected natural political translated texts (from English into Arabic) through the employment of contrastive textual analytical method. The study emphasizes conclusively that textuality standards are effective tools for the assessment of global text function and thus serve in the (de)construction of the real translation. It also observes that each element of the standards reflects and demonstrates various ways text functions are linguistically, textually and communicatively realized in the structures of selected translated texts. The political texts translators appeared to have succeeded in conveying the syntactic, semantic, stylistic, pragmatic aspects of the source texts and the conclusion is that the translated texts might be accepted as equivalent texts. The thesis therefore suggests among others, that the standards of textuality be seriously integrated in translation studies as a cognitive frame of reference through a contrastive method for the analysis and evaluation of translated texts.